2021
DOI: 10.7717/peerj.12608
|View full text |Cite
|
Sign up to set email alerts
|

The cost of a meal: factors influencing prey profitability in Australian fur seals

Abstract: Knowledge of the factors shaping the foraging behaviour of species is central to understanding their ecosystem role and predicting their response to environmental variability. To maximise survival and reproduction, foraging strategies must balance the costs and benefits related to energy needed to pursue, manipulate, and consume prey with the nutritional reward obtained. While such information is vital for understanding how changes in prey assemblages may affect predators, determining these components is inher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…While this could reflect an increase in prey encounters due to changes in search direction (Bell, 2012), the directional changes may reflect intentional movements towards detected prey (Bianco et al, 2011). Indeed, previous studies of AUFS instrumented with animal-borne video cameras have revealed individuals often make sharp turns upon detecting prey with a high degree of capture success (73%) (Meyers et al, 2021). However, without additional video data, it is not possible to disentangle the observed relationship between prey capture rate and directional changes during sea floor searches by AUFS.…”
Section: Within-dive Behaviour To Optimise Benthic Foraging Successmentioning
confidence: 99%
See 1 more Smart Citation
“…While this could reflect an increase in prey encounters due to changes in search direction (Bell, 2012), the directional changes may reflect intentional movements towards detected prey (Bianco et al, 2011). Indeed, previous studies of AUFS instrumented with animal-borne video cameras have revealed individuals often make sharp turns upon detecting prey with a high degree of capture success (73%) (Meyers et al, 2021). However, without additional video data, it is not possible to disentangle the observed relationship between prey capture rate and directional changes during sea floor searches by AUFS.…”
Section: Within-dive Behaviour To Optimise Benthic Foraging Successmentioning
confidence: 99%
“…Pelagic foragers use the entirety of the dive in search of prey (Arnould and Costa, 2006), exploiting highdensity patches of small schooling species (fish, crustacea and cephalopods) which can be distributed throughout the water column (Chimienti et al, 2017). In contrast, benthic foragers search for larger, cryptic prey on the seafloor (Meyers et al, 2021). The high energetic costs of diving to the sea floor (Costa, 1991) are balanced by the profitability of spatial and temporal predictability of benthic prey abundance and distribution (Arnould and Costa, 2006).…”
Section: Introductionmentioning
confidence: 99%